Environmental ideology in WALHI’s ecological disaster press releases: An ecolinguistic analysis of Sumatra - Mimas Ardhianti; Eko Cahyo Prawoto; Antok Risaldi (NOTION: Journal of Linguistics, Literature, and Culture, 2026)
This study aims to uncover the environmental ideology embedded in WALHI’s ecological disaster press releases through transitivity analysis. The study employs a descriptive qualitative approach grounded in ecolinguistics within the framework of Systemic Functional Linguistics (SFL). The data consist of press releases on ecological disasters in Sumatra published by Wahana Lingkungan Hidup Indonesia (WALHI). Data were collected through observation and documentation techniques. The collected data were analyzed in four stages: (1) clause segmentation and numbering; (2) identification and classification of process types; (3) identification of participant roles and circumstantial elements; and (4) interpretation of ideological patterns based on recurring configurations of processes and participants. The findings indicate that relational processes dominate the transitivity patterns, followed by material, existential, verbal, mental, and behavioral processes. The environmental ideologies identified in WALHI’s ecological disaster press releases include: (1) environmental ideology: those in power are responsible for environmental destruction; (2) environmental ideology: rejection of power practices in elite regulations; (3) environmental ideology: justice in resisting systems of power; (4) environmental ideology: the government must be responsible for environmental damage; and (5) environmental ideology: transparent enforcement of legal policies.